The Linguistic Rooting of Hate Speech: Analytical Study in the Legal Achievement - Agrine, Meriem (LANGUAGE ART, 2023)
Hate speech often targets specific groups and minorities, making it a pressing issue amidst global political and economic turmoil. This speech employs insulting language to dehumanize and defame those who are intellectually different. Its danger lies in its ability to spread rapidly, fostering intolerance and hatred, which often leads to aggressive behavior resulting in personal tragedies or mass atrocities. Despite the ambiguity and debate surrounding the term, and the lack of a precise legal definition, it now refers to a wide spectrum of behaviors, ranging from tolerated offensive speech to criminally punishable acts. From this standpoint, this paper aims to conduct an in-depth analysis of this phenomenon through a multidisciplinary approach, seeking to establish a foundational understanding of the concept within its linguistic and legal contexts. It aims to provide a methodological framework for distinguishing between "hate speech" and "hate crime" by analyzing prevailing linguistic standards. The study concluded that feelings of hatred themselves are not a crime; rather, the basis for criminalization is linked to the symbolic dimension of the speech. The perpetrator sends an exclusionary message not only to the direct victim but also to the community they belong to. The study also presented a hierarchical semantic scale for analyzing the "intensity" and "severity" of such speech, positing that hate crimes are "message crimes" designed to entrench "otherness" and influence the structure of marginalized social groups.